Resilience and Academic Self-Concept as Explanatory Variables of Achievement Motivation Among College Students - Angelina Abaidoo; Isaac Amoako; Inuusah Mahama; Opoku Boahen Edward (European Scientific Journal, ESJ, 2021)
People with high achievement motives will act in ways that will help them to outperform others, meet or surpass some standards of excellence, or do something unique. Several variables have been suggested in the literature to significantly contribute to students’ achievement motivation. As the principal aim, the study sought to investigate whether or not resilience and academic self-concept significantly contribute to students’ achievement motivation. A cross-sectional research design was employed to sample 327 first year college students from five College of Education institutions in Ghana using proportionate stratified sampling procedure. Three instruments (i.e., resilience scale, academic self-concept scale and achievement motivation scale) were adapted and used for the study. Findings of the study showed that students’ sampled were resilient and had high academic self-concept. The results further showed that resilience and academic self-concept variables were significant predictors of achievement motivation. The study recommends that academic counseling within Colleges of Education in Ghana should be made a priority in order to address issues of self-doubt and that of learned helplessness, particularly to maintain or improve individual resilience and achievement motivation. Other implications are discussed.